Piperlongumine analogue L50377 induces pyroptosis via ROS mediated NF-κB suppression in non-small-cell lung cancer. (1st November 2019) - Li, Qian; Chen, Liping; Dong, Zhaojun; Zhao, Ya; Deng, Hui; Wu, Jianzhang; Wu, Xiaoping; Li, Wulan
Abstract: Natural products with potent activity and less toxicity provide major sources for development of novel anti-cancer drugs. Herein, we evaluated the effects and the underlying mechanisms of a novel piperlongumine (PL) analogue L50377 on non-small-cell lung cancer (NSCLC) cells. The results revealed that L50377 displayed greater potentials of suppressing cell growth than PL. In addition, L50377 promoted cell apoptosis and pyroptosis via stimulating reactive oxygen species (ROS) generation in NSCLC cells. More interestingly, ROS mediated NF-κB suppression might be implicated in the mechanisms of L50377-induced pyroptosis in NSCLC cells. Taken together, our results suggested that L50377 served as a novel chemical agent might have great potentials for NSCLC treatment. Graphical abstract: Image 1 Highlights: Piperlongumine (PL) analogue L50377 exhibits potent inhibitory effects on NSCLC. L50377 promoted cell apoptosis and pyroptosis via stimulating reactive oxygen species (ROS) generation in NSCLC cells. ROS mediated NF-κB suppression might account for the mechanisms of L50377-induced pyroptosis in NSCLC cells.